Socio-economic Impacts of Rural Energy Poverty on Women and Students in Esa-Oke, Nigeria - Famewo, Ayomide Samuel; Uwala, Vincent Abimbola (Journal of Sustainability and Environmental Management, 2022)
Energy poverty is a growing global challenge with significant adverse effects on well-being and health. However, its social impacts on vulnerable population in deprived communities have been largely ignored. Consequently, this study examines the social-economic impacts of energy poverty among women and students in Esa Oke, a hilly and rural and energy-deprived community in southwestern Nigeria. A cross-sectional survey design approach was adopted, while purposive and random sampling technique was used in selecting respondents. Findings from the study revealed differences in energy consumption behaviour of women and students in rural settings; while women adopt traditional biomass for cooking, students adopt modern energy services. Additionally, the impacts of poor energy access differ per women and students. For instance, on one hand, the use of traditional biomass significantly affects rural women's health, as the majority (95%) of women respondents reported exposure to emissions through indirect combustion of fuelwood. On the other hand, students' academic performance and academic activities were significantly disrupted due to the poor electricity supply in the area. Based on the foregoing, the study recommends an inclusive rural energy policy that captures all social groups affected by energy poverty.